Characterization of molecular mechanisms underlying the axonal Charcot–Marie–Tooth neuropathy caused by MORC2 mutations. (8th January 2019) - Sancho, Paula; Bartesaghi, Luca; Miossec, Olivia; García-García, Francisco; Ramírez-Jiménez, Laura; Siddell, Anna; Åkesson, Elisabet; Hedlund, Eva; Laššuthová, Petra; Pascual-Pascual, Samuel I; Sevilla, Teresa; Kennerson, Marina; et al.
Abstract: Mutations in MORC2 lead to an axonal form of Charcot–Marie–Tooth (CMT) neuropathy type 2Z. To date, 31 families have been described with mutations in MORC2, indicating that this gene is frequently involved in axonal CMT cases. While the genetic data clearly establish the causative role of MORC2 in CMT2Z, the impact of its mutations on neuronal biology and their phenotypic consequences in patients remains to be clarified. We show that the full-length form of MORC2 is highly expressed in both embryonic and adult human neural tissues and that Morc2 expression is dynamically regulated in both the developing and the maturing murine nervous system. To determine the effect of the most common MORC2 mutations, p.S87L and p.R252W, we used several in vitro cell culture paradigms. Both mutations induced transcriptional changes in patient-derived fibroblasts and when expressed in rodent sensory neurons. These changes were more pronounced and accompanied by abnormal axonal morphology, in neurons expressing the MORC2 p.S87L mutation, which is associated with a more severe clinical phenotype. These data provide insight into the neuronal specificity of the mutated MORC2-mediated phenotype and highlight the importance of neuronal cell models to study the pathophysiology of CMT2Z.